2009
DOI: 10.1016/j.ejpain.2008.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term oral lacosamide in painful diabetic neuropathy: A two‐year open‐label extension trial

Abstract: The long-term safety profile and sustained efficacy of lacosamide observed in this trial support its continued development for treatment of painful diabetic neuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 23 publications
0
17
0
1
Order By: Relevance
“…[21][22][23] All the studies showed a small reduction in pain with 400 mg/day of lacosamide (3%, 6%, and 6% compared to placebo), but in 2 studies no significant differences compared to placebo were observed with 600 mg/day of lacosamide. 22,23 In one study, benefits on general activity and sleep interference QOL measures were observed. 21 Conclusions.…”
Section: Analysis Of Evidence In Patients With Pdnmentioning
confidence: 99%
“…[21][22][23] All the studies showed a small reduction in pain with 400 mg/day of lacosamide (3%, 6%, and 6% compared to placebo), but in 2 studies no significant differences compared to placebo were observed with 600 mg/day of lacosamide. 22,23 In one study, benefits on general activity and sleep interference QOL measures were observed. 21 Conclusions.…”
Section: Analysis Of Evidence In Patients With Pdnmentioning
confidence: 99%
“…Three Class III studies evaluated the efficacy of lacosamide 21–23. All the studies showed a small reduction in pain with 400 mg/day lacosamide (3%, 6%, and 6% compared with placebo), but in two studies no significant differences compared with placebo were observed with 600 mg/day lacosamide 22, 23. In one study, benefits on general activity and sleep interference QOL measures were observed 21…”
Section: Analysis Of Evidencementioning
confidence: 99%
“…Several clinical trials have confirmed its analgesia effect for painful DPN treatment [52]. Furthermore, long-term safety profile and sustained efficacy of lacosamide have been demonstrated in an open-label follow-on trial followed the DPN patients application of lacosamide up to about 2.5 years [53]. …”
Section: Other Therapeutic Approaches and Novel Drug Targetsmentioning
confidence: 99%